2019
DOI: 10.1021/acs.jpcc.9b08369
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Hydration of Xenon and Tetrahydrofuran in Amorphous Solid Water

Abstract: On the basis of temperature-programmed desorption (TPD), interactions of water with polar (tetrahydrofuran (THF)) and nonpolar (Xe) additives were investigated on the surfaces of bare, oxygenated, and CO-chemisorbed Pt(111) substrates, together with amorphous solid water (ASW) and crystalline ice films. The influences of these additives on the crystallization kinetics of water were discussed based on reflection high-energy electron diffraction. The Xe adspecies is hydrated by a water monolayer on the clean and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It might be presumed that the sharp peaks A and B are indicative of the formation of crystalline CHs. However, no long-range ordering is identified in electron diffraction patterns during the heating process of the composite films till ice Ic is formed at T c = 160 K. 54 The results for crystallization kinetics are fundamentally identical to those using pure ASW films. This is reasonable because most of the nonpolar additives are released in the liquidlike phase prior to crystallization as demonstrated here.…”
Section: Discussionmentioning
confidence: 74%
“…It might be presumed that the sharp peaks A and B are indicative of the formation of crystalline CHs. However, no long-range ordering is identified in electron diffraction patterns during the heating process of the composite films till ice Ic is formed at T c = 160 K. 54 The results for crystallization kinetics are fundamentally identical to those using pure ASW films. This is reasonable because most of the nonpolar additives are released in the liquidlike phase prior to crystallization as demonstrated here.…”
Section: Discussionmentioning
confidence: 74%
“…For example, some experiments have investigated the behavior of DMSO in situ /operando for battery applications. , Some of the fundamental experiments on interactions of solvent molecules with transition metal surfaces have also been carried out as part of studies of metal-catalyzed reactions; for example, spectroscopic observations of THF on Pt(111) were made as part of a study on furan hydrogenation, finding evidence for the upright structure of THF on Pt. A recent study reported experiments on the interactions between THF and water on Pt(111), though this work focused primarily on hydration interactions rather than specific THF-metal interactions. THF adsorption has also been studied on Cu(111), finding evidence that THF adsorbs significantly more strongly on Cu than does its aromatic counterpart, furan.…”
mentioning
confidence: 99%